Kegiatan Meronce untuk Perkembangan Motorik Halus Anak Usia Dini pada Kelompok A Di KB at-Taufiq Desa Cihanjawar - Chintia Pebriyanti Chintia; Sofia Gussevi (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2023)
Community Service Lecture (KPM) is one of the dharma activities at STAI DR. KH. EZ. Muttaqien Purwakarta. This KPM activity is a service activity carried out by final semester students to the community. In this KPM, a program is implemented, namely